Have Cook Book, Will Travel - Cullen, Paula (Petits Propos Culinaires, 2025)
Food history studies often refer to evidence provided by travel books which relate experiences of food in foreign countries in past times. The essay primed here is a comparatively recent one (it originally appeared in The Lady in 1971), but recent history is just as fascinating as that of the more distant past, and Paula Cullen gives a lively conspectus of foods eaten in many countries, mainly African, by a peripatetic entomologist, working mainly for the World Health Organization, and his wife.